Positive leadership for flourishing schools - Walker, Keith D. 1954-; Kutsyuruba, Benjamin; Cherkowski, Sabre, 1970- (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Most educators will agree that they'd love to see each student and staff member in schools flourish; and, further, that to see entire communities might experience the transformative power of circumstances that feature happy and vibrant learning would be great. What does it mean to experience flourishing in schools? What is the role of positive leadership in this process? What can we learn from inquiring into the positive emotional and social aspects of the work of school leaders? Building on our research on flourishing in schools, this book highlights the stories and perspectives of educators and school leaders at all levels of the school system and demonstrate the intricacies of how positive leadership contributes to well-being in schools and encourages flourishing in these schools. This book aligns with a growing shift in psychology and organizational studies to frame research using phenomena and constructs such as resilience, compassion, hope, efficacy, self-determination and meaningfulness at work and in other areas of life. Research findings from the disciplines of both positive psychology and positive organization studies bring these positive research intelligences into the field of education to study what about school leadership practices work, what goes well, what supports and what brings vitality to people in school organizations. Research in positive psychology contends that attending to the strengths, positive outlooks, habits and mental models, as opposed to a deficit-oriented perspective, is beneficial to increasing subjective well-being, by increasing resilience, vitality, and happiness and decreasing stress, anxiety, and depression. How we imagine leading, teaching and learning in schools are implicated in these understandings and help us to contemplate the benefits of focus positive leadership in school organizations. Powerful insights into human inquiry and positive psychology are gained through qualitative study and most of the chapters of this book are grounded in such research. Importantly, chapters in this book provide a varied repertoire of answers to the question that underpins this shift in research toward a positive organizational perspective: How does positive leadership leverage what works well to instill in each community member a sense of their value and capacity to contribute, encourage wellbeing for all and create school contexts of flourishing? This edited collection provides many examples, invitations, and inspiration for readers to notice in their own contexts in ways that encourage them to shift and grow through moving toward appreciative, strengths-based, positive approaches to teaching, learning, and, especially, leading in all school contexts"--